Knowledge, Attitude, and Practice Toward Infection Prevention Strategies Pre- and Post-COVID-19 Among Nursing Students: A Systematic Review - Fithriyyah, Yayu Nidaul; Alim, Syahirul (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Aims: COVID-19 (Coronavirus Disease 2019) has significantly impacted infection control, highlighting the vulnerabilities of the global healthcare system. This study evaluates measurable outcomes and barriers in nursing students' knowledge, attitudes, and practices, and barriers to infection prevention before and after COVID-19. Method: systematic review, with the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) registered on PROSPERO: CRD42022322706. Using the PICO framework for article selection: Population (involving nursing students), Intervention/exposure (infection control or prevention), Compare and Outcome (knowledge, attitudes, and practice). We searched nine databases from March to June 2022, with inclusion criteria for full-text articles published in English from 2012 to 2022. The study quality used The Joanna Briggs Institute (JBI) Critical Appraisal tool and the National Institutes of Health (NIH). PICO synthesis for analysis. Results: Of 3,030 articles, only 15 met the criteria for inclusion: Cross-sectional (12/15, 80%), Descriptive study (2/12, 13%), and pre-post study (1/15, 6.67%). Infectious disease (4/15, 26.6%) and All disaster events (4/15, 26.6%), with the condition: pre-COVID-19 (11/15,73.3%), and during COVID-19 (4/15, 26.6%). The five themes were: (1) nursing students' knowledge level regarding infection control standards, (2) nursing students' attitudes towards infection control standards, (3) nursing students' practice on infection control standards, (4) factors affecting infection control in nursing students, (5) roles of nursing schools and hospitals in infection control. Conclusion: Nursing students showed increased knowledge, but gaps in attitudes and practice remain. Future efforts should develop standardized infection prevention curricula, integrate social media training, and strengthen academic-healthcare partnerships.